Analysis of anthropic interference in the quality of surface water in the Cotia River Basin (SP) - Toniolo, Bruno Pereira [UNESP]; Simonetti, Vanessa Cezar [UNESP]; Lourenço, Roberto Wagner [UNESP]; Da Cunha e Silva, Darllan Collins [UNESP] (University Nove de Julho, 2024)
Objective: To seasonally evaluate the water quality of the Cotia River Basin (CRB) by the Water Quality Index (WQI) between 2002 and 2018, correlating it with the classes of land use and occupation existing in this basin. Methodology: Data from the Environmental Company of São Paulo State were used from 2002 to 2018 in five contribution areas (CAs) of the CRB (P1 to P5), calculating the WQI for the dry and rainy seasons. The Anthropic Transformation Index (ATI) was calculated and it was related to the WQI through Pearson's correlation. Originality/Relevance: Take advantage of data from a monitored watershed to determine, from a historical series, the water quality as a function of quantifying the deleterious effects of human action. Results: The average WQI of the CRB was classified as Regular for both analyzed periods, with distinction between the CAs, so that P5, corresponding to the Morro Grande Forest Reserve (MGFR), has Excellent quality, while those with anthropized areas presented WQI varying between Regular and Bad. The ATI classified the basin as having medium degradation and the MGFR as having weak degradation, however the anthropic CAs alternated between medium and strong degradation. The linear correlation between the ATI and the WQI confirmed that the anthropic classes of land use influence the opposite way in the water quality, being corroborated by the values of the parameters Dissolved Oxygen (DO), Biochemical Oxygen Demand (BOD) and Total Phosphorus (TF) that were outside the limits established by Resolution 357/2005 of the National Council for the Environment. Contributions: The study showed that the behavior of water quality in the CAs acts in a heterogeneous way, revealing that the most anthropized areas of the basin are influencing the water quality, serving as support in the context of water resources management.
Análisis de la interferencia antrópica en la calidad del agua superficial en la Cuenca del Río Cotia (SP)
Análise da interferência antrópica na qualidade das águas superficiais da Bacia Hidrográfica do Rio Cotia (SP)
Keywords: geoprocessing; indicator; sanitation; water pollution